High extinction ratio magneto-optical fiber modulator based on nanoparticle magnetic fluids - Dong, Xinyong (2013)
A novel magneto-optical fiber modulator with a high extinction ratio (ER) based on a polarization interference structure is proposed. A magnetic fluid (MF) film and a section of a polarization-maintaining fiber (PMF) are inserted into the structure to generate a suitable sinusoidal interference spectrum for light modulation. The MF film leads to a spectrum shift under external magnetic field due to its magnetically controllable birefringence, whereas the PMF is used to control the period of the interference spectrum. In this experiment, magneto-optical modulation with a high ER of 38 dB is demonstrated.